Effect of Xanthone and 1-Hydroxy Xanthone on the Dipole Potential of Lipid Membranes - Cejas, Jimena del Pilar (2018)
Xanthone (Xa) and 1-OH Xanthone (1-OHXa) in 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) membranes increase the dipole potential. Results with 1,2-di-O-tetradecyl-sn-glycero-3-phosphocholine (Ether PC), lacking carbonyl groups, indicate that the CO dipole of Xa molecule does not contribute to the increase of dipole potential. Molecular Dynamics calculations confirm that CO group of Xa locates parallel to the membrane interphase. Xa decreases the area per lipid in DPPC monolayers and the membrane polarity as measured by GP of Laurdan explaining the dipole potential increase. This rearrangement of water in the CO region is consistent with Fourier Transform Infrared Spectroscopy results indicating that CO of Xa are buried in the membrane phase. In contrast, CO groups of DPPC show an additional population of bound COs that seems to be more exposed to water, which contributes to the increase in dipole potential. These results are also corroborated by MD simulations.